PERBANDINGAN SIFAT FISIK TABLET SALUT CIPROFLOXACIN 500 MG MEREK GENERIK DAN MEREK DAGANG - Mikhania C.E., Dewi rashati, Dadang Putra Mardigantara (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2016)
The aim of this study was to compare physical properties ciprofloxacin 500 mg coated tablet generic and trademark brand. The test include weight uniformity, tablet hardness, tablet friability, and disintegration time test. Descriptive experimental design (the one-shot case study) was used as study design. Samples were taken from three generic brands and three trademarks brand ciprofloxacin 500 mg coated tablets. Samples were produced by different factories and taken by simple random sampling method. The results showed that ciprofloxacin 500 mg coated tablets generic and trademark brand are comparable unless hardness of tablet.Keywords: Ciprofloxacin 500 mg, Physical Properties Tablet, Generic and Trademark Brand